Challenging Thoughts, Changing Minds: Preservice Teachers' Reflections on Their Experience Working in an Alternative School Setting. Issue 4 (2nd October 2017) - Blevins, Brooke; Moore, Brandon; Dexter Torti, Cameron
ABSTRACT: This study was designed to use critical reflective journaling practices to explore the experiences of preservice teachers working in a juvenile justice education program called the Reach Academy. Using a qualitative case study design, the researchers explored how 48 preservice teachers utilized critical reflective journaling to examine their own identities in relation to working in this unique school setting. Three major themes emerged from the reflective journal and interview data: (a) participants preconceived notions were challenged based on their positive interactions with Reach students, (b) preservice participants engaged in critical observation of the Reach Academy teachers and their interactions with students, and (c) participants' focus shifted from themselves to their students' needs. Findings suggest that preservice teachers reflective journaling process facilitated their ability to examine and reconsider their preconceived notions about working with students at the Reach Academy and in other diverse schooling settings.